Safety and efficacy of a feed additive consisting of concentrated liquid l‐lysine, l‐lysine monohydrochloride and concentrated liquid l‐lysine monohydrochloride produced by Escherichia coli NITE BP‐02917 for all animal species (Metex NoovistaGo). (25th October 2022) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of concentrated liquid l ‐lysine, l ‐lysine monohydrochloride and concentrated liquid l ‐lysine monohydrochloride produced by Escherichia coli NITE BP‐02917 as nutritional and as sensory (flavouring compound) feed additives for all animal species. The production strain did not carry ■■■■■ antimicrobial resistance genes and no viable cells of the production strain were detected in the final products. ■■■■■ However, since no sequences of concern remained in the production strain, the potential presence of that DNA did not raise safety concerns. The use of the three forms of l ‐lysine produced by E. coli NITE BP‐02917 in supplementing feed to compensate for l ‐lysine deficiency in feedingstuffs was safe for the target species. This conclusion would also cover the use as a sensory additive. The FEEDAP Panel identified risks of nutritional imbalances and hygienic concerns for amino acids when administered simultaneously in feed and in water for drinking. The use of the three forms of l ‐lysine produced by E. coli NITE BP‐02917 in animal nutrition was considered safe for the consumers and for the environment. Concentrated liquid l ‐lysine, l ‐lysine HCl and concentrated liquid l ‐lysine HCl were not considered to have the potential to cause respiratory toxicity, or skin sensitisation. l ‐Lysine HCl and concentrated liquid l ‐lysine HCl were not considered skin and eye irritants. Concentrated liquid l ‐lysine, due to its high pH, might be corrosive for skin and eyes. The three forms were considered an efficacious source of the essential amino acid l ‐lysine for non‐ruminant animal species. For the supplemental l ‐lysine to be as efficacious in ruminants as in non‐ruminant species, it would require protection against degradation in the rumen. The three forms of the additive were also considered efficacious as feed flavouring compounds under the proposed conditions of use.